Granito Serra da Queimada, Suíte Intrusiva Velho Guilherme, Província Carajás: tipologia, aspectos petrológicos e afinidades metalogenéticas. - MELO, Lucas Maurício Condurú (Universidade Federal do Pará, 2020)
The Serra da Queimada Granite (GSQ) is a subcircular paleoproterozoic anorogenic batholith, approximately 20 km2 in area, located north of the city of São Félix do Xingu, in the Carajás Province, southeast of the Amazonian Craton. It splits archean units of the São Félix Group and paleoproterozoic groups of the Iriri Group, Uatumã Supergroup. It is formed by three distinct petrographic facies: syenogranite biotite (BSG), monzogranite biotite (BMG) and porphyritic syenogranite (SGP), all with graphics content<10%. The frequent occurrence of spherulitic and granopyric intergrowths suggests that GSQ rocks crystallized at shallow crustal levels. Electron probe analysis showed that GSQ biotites are predominantly magmatic, ferrous and Al-enriched. Total rock geochemical analyzes showed that GSQ is peraluminous to weakly metaluminous, FeOt/(FeOt +MgO) ratios between 0.75 and 0.99 and K2O/Na2O between 0.6 and 2.3; shows geochemical affinities with intra-plate A type granites, of subtype A2, and ferrous granites, suggesting a crustal source for their origin. It has higher light rare earth element contents than heavy rare earth elements, with a sub-horizontal pattern for the latter, as well as increasing negative Eu anomalies towards the more evolved BSG facies. The geochemical data show that BSG have higher average K2O, Y, Rb, W and Sn content and lower TiO2, Fe2O3, MgO, CaO, Ba and Sr than other facies, typical characteristics of specialized granites. Crystallization temperatures based on the Zr saturation geothermometer indicated ranges between 754 °C and 870 °C, similar to other anorogenic granites in the Carajás Province. Comparative geological, petrographic, mineral chemistry and geochemical studies between the GSQ and other specialized granites belonging to the Velho Guilherme Intrusive Suite indicate that sienogranitic rocks of the GSQ show potential for mineralization in W and Sn and that it can be framed in the geological context of this important granite suite.